THE EFFECT OF EDMODO – BASED BLENDED LEARNING ON ACCOUNTING LEARNING OUTCOMES VIEWED SELF REGULATED LEARNING - Abidah Dwi Rahmi Satiti; Yenni Vera Fibriyanti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The objective of this research was to investigate the difference effect between the Edmodo - Based Blended Learning and the conventional learning on accounting learning outcomes viewed self regulated learning. This research was an quasi experimental with nonequivalent pretest posttest control-group design. The population of research was the students in semester 4 of classes A, B, and C. The research sample was taken 2 classes, namely class B and class C.  The data were analyzed by using the two-way analysis of variance and was continued with the Scheffe test. The findings showed that: (1) there was a difference effect between the Edmodo –Based Blended Learning on accounting learning outcomes; (2) there was a difference effect of the high, moderate, and low self regulated learning on accounting learning outcomes; and (3) there was not an interaction between the Edmodo – Based Blended Learning and the conventional learning with self regulated learning on accounting learning outcomes.